The Body as a Private and Social Space. The Margins of Research Regarding Old Age and Gender - Bieńko, Mariola (Qualitative Sociology Review, 2018)
In the conditions of late modernity, the body is a project realized in both the public and private spheres. The aim of this article is to review theories and empirical studies concerning socio-cultural issues and the subjective determinants of perceptions of physicality. The body has become the main instrument of experiencing the world and oneself, a significant area, a key element of an individual’s identification strategy. The modern human speaks with and through the body, the person’s identity is reduced to self-presentation, by projecting their physicality, they project themselves. The presentation and reception of body is dominated by an aesthetic perspective, organically bound with the tendency to aestheticize daily life in general. The text is based on empirical data, analysis of 403 qualitative interviews conducted between 2012-2014 in Polish cities: Warsaw, Kielce, Chelmno, and Przemysl. The research shows that the emotional aspect of experiencing body, as well as the cognitive aspect within consciousness, the mental image of one’s own body, differ according to the respondents’ age and gender.